MiR-148a-3p Regulates Skeletal Muscle Satellite Cell Differentiation and Apoptosis via the PI3K/AKT Signaling Pathway by Targeting Meox2 - Yin, Huadong; He, Haorong; Cao, Xinao; Shen, Xiaoxu; Han, Shunshun; Cui, Can; Zhao, Jing; Wei, Yuanhang; Chen, Yuqi; Xia, Lu; Wang, Yan; Li, Diyan; et al. (Frontiers in Genetics, 2020)
As bioinformatic approaches have been developed it has been demonstrated that microRNAs (miRNAs) are involved in the formation of muscles, and play important roles in regulation of muscle cell proliferation and differentiation. Previously it has been demonstrated that miR-148a-3p is one of the most abundant miRNAs in chicken skeletal muscle. Here, we build on that work and demonstrate that miR-148a-3p is important in the control of differentiation of chicken skeletal muscle satellite cells (SMSCs). Elevated expression of miR-148a-3p significantly promoted differentiation and inhibited apoptosis of SMSCs but did not affect proliferation. Furthermore it was observed that the mesenchyme homeobox 2 (Meox2) is a target gene of miR-148a-3p and that miR-148a-3p can down-regulate expression of Meox2, which promote differentiation of SMSCs and suppress apoptosis. Furthermore, miR-148a-3p overexpression encouraged activation of the PI3K/AKT signaling pathway, which could be recovered by overexpression of Meox2. Overall, these findings suggest microRNA-148a-3p is a potent promoter of myogenesis via direct targeting of Meox2 and increase of the PI3K/AKT signaling pathway in chicken skeletal muscle satellite cells.